RAIKU: E-Commerce App Using Laravel - Salsabila Nurulfarah Mahmudah; Bana Handaga; Reza Armando Wibowo (IAES Indonesia Section, 2020)
Raiku is an e-commerce site-based app which developed with Laravel. The function of this app is to expand marketing network of Raiku Design business. After 2 months Raiku been hosting, there is an increase on the world visitors’ numbers about 557 people. It is not only accessed by Indonesian, but also accessed around the world such Canada, United States, Australia, Germany, Great Britain, Chile, Russian Federation, India, China, South Korea, Israel, Netherlands, Ireland, Italy, and there are still more.